Evaluation of Patient Experience with a Model of Coordinated Telematic Pharmaceutical Care Between Hospital and Rural Pharmacies in Spain [Letter] - Kolomboy F; Condeng B; Duyoh L (Journal of Multidisciplinary Healthcare, 2023)
Fajrillah Kolomboy,* Baharuddin Condeng,* Lenny Duyoh* Department of Nursing, Poltekkes Kemenkes Palu, Palu, Indonesia*These authors contributed equally to this workCorrespondence: Fajrillah Kolomboy, Faculty of Nursing, Poltekkes Kemenkes Palu, Thalua Konchi Street Number 09, North Palu, Palu, Center Sulawesi, Indonesia, Email fajrillah73@gmail.com